New Advances in Targeted Therapy of HER2-Negative Breast Cancer - An, Junsha; Peng, Cheng; Xie, Xiaofang; Peng, Fu (Frontiers in Oncology, 2022)
Breast cancer has an extremely high incidence in women, and its morbidity and mortality rank first among female tumors. With the increasing development of molecular biology and genomics, molecular targeted therapy has become one of the most active areas in breast cancer treatment research and has also achieved remarkable achievements. However, molecular targeted therapy is mainly aimed at HER2-positive breast cancer, and has not yet achieved satisfactory curative effect on HER2-negative breast cancer. This article describes the potential targets that may be used for breast cancer treatment from the aspects of PI3K/AKT signaling pathway, DDR, angiogenesis, the cell cycle, breast cancer stem cells, etc., and explores possible inhibitors for the treatment of HER2-negative breast cancer, such as PI3K inhibitors, AKT inhibitors and m-TOR inhibitors that inhibit the PI3K/AKT signaling pathway, small molecule tyrosine kinase inhibitors that restrain angiogenesis, CDK inhibitors, aurora kinase inhibitors and HDAC inhibitors that block cell cycle, as well as the drugs targeting breast cancer stem cells which have been a hit, aiming to provide a new idea and strategy for the treatment of HER2-negative breast cancer.